Safety of Poznań residents after 1989 (selected aspects) - Mierzejewska, Lidia (Rozwój Regionalny i Polityka Regionalna, 2015)
Safety is one of the fundamental human needs which greatly affects the quality of people’s lives. It is also a collective need the satisfaction of which is a task of public authority. That is why this authority takes many measures intended to protect society and individuals as well as their property against threats posed by violent acts of people and violent natural forces. According to the Polish legal regulations, ensuring safety and public order is a task of a commune, also an urban one. To this end towns set up such services as the police, the fire brigade, emergency medical teams, city guards, etc., intended to serve their inhabitants. Their feeling of safety and a low crime rate are indicative of a town’s high level of civilisational and cultural development, but also make the town attractive as a place of residence for both, current and future inhabitants as well as to potential investors. The aim of this paper is to examine selected aspects of the safety of Poznań residents and changes that have taken place in this respect since 1989, the year when the systemic transformation started in Poland. A detailed analysis will be made of interventions by the Poznań police, fire service and ambulance service as factors that contribute the most to the safety of the city residents and their property.